Validação da versão brasileira do Functional Assessment of Cancer Therapy-Prostate (FACT-P, versão 4) em homens com câncer de próstata não metastático : Validation of the brazilian version of Functional Assessment of Cancer Therapy-Prostate (FACT-P, version 4) in men with nonmetastatic prostate cancer - Held, Priscila Antonichelli de, 1985- (2018)
Orientador: Wagner Eduardo Matheus